Food intolerance and Crohn's disease. - Pearson, M (1993)
It has been claimed that prolonged remissions of Crohn's disease can be achieved after enteral or parenteral nutrition, by identifying and excluding foods that exacerbate a patient's symptoms. The occurrence of food intolerances were assessed after induction of remission with elemental diet in 42 eligible patients to whom single foods were introduced over five days. Suspect foods were reinvestigated with open and if possible, double blind rechallenge. Fourteen patients (33%) dropped out of the study because of relapse of disease unrelated to food (n = 8) or because of difficulties in complying with the regimen (n = 6). Twenty (48%) of the patients identified food sensitivities whereas eight (19%) did not. Seventeen of the patients who identified food sensitivities had an open rechallenge with recurrence of symptoms in 10 (24% of total). Food sensitivity was confirmed in three patients on double blind challenge. There was no significant difference in the duration of remission between patients who did or did not identify food sensitivities. During the study three cases of intolerance to the formula diet, and one of severe salicylate sensitivity were encountered. In conclusion food sensitivities are evident after treatment of Crohn's disease with elemental diet but are variable, often do not persist, and are of insufficient importance to warrant putting all patients through elimination diets.